2021
DOI: 10.1111/jgs.17141
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity moderates the effect of sedentary time on an older adult's physical independence

Abstract: Background/objectives Moderate‐to‐vigorous physical activity (MVPA) and breaks in sedentary time (BST) have been proposed as viable solutions to improve an older adult's physical independence, whereas sedentary time (ST) has been associated with detrimental effects. We sought to assess the joint effects of ST, BST, and MVPA on the physical independence of older adults and determine whether and to what extent the ST relationship with physical independence is moderated by MVPA and/or BST. Design Cross‐sectional.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 21 publications
(60 reference statements)
0
17
0
6
Order By: Relevance
“…A possible explanation is that a stronger stimulus than a muscular contraction originates from a break in sedentary time may be needed to induce an improvement in physical function outcomes, such as handgrip strength and lower limb strength [ 32 ]. Furthermore, a previous study also indicated that a break in sedentary time was not related to subjective physical function, taking into account MVPA and the duration of the sedentary period [ 33 ]. Another possible explanation for the non-significant associations found in our study could be that the participants’ characteristics [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is that a stronger stimulus than a muscular contraction originates from a break in sedentary time may be needed to induce an improvement in physical function outcomes, such as handgrip strength and lower limb strength [ 32 ]. Furthermore, a previous study also indicated that a break in sedentary time was not related to subjective physical function, taking into account MVPA and the duration of the sedentary period [ 33 ]. Another possible explanation for the non-significant associations found in our study could be that the participants’ characteristics [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…28 A limitation to this investigation is its cross-sectional design, which does not allow for the establishment of causality, nor the exclusion of reverse causality in the relationships between STS relative muscle power and projected physical independence. Moreover, although the CPF scale has been validated 13 and used in previous studies to assess physical independence of older adults, 10,11,29,30 it is based off of self-report, which could have biased results. Having a longitudinal approach would allow for a more precise determination of the minimum relative STS power levels necessary to maintain physical independence in old age.…”
Section: Discussionmentioning
confidence: 99%
“…sedentary time (ST), which have previously been shown to be strong predictors of an older adult's physical independence, 10,11 remains to be analyzed. This investigation aimed to assess the predictive ability of STS relative muscle power to determine an older adult's projected physical independence at age of 90 yrs beyond that of relative handgrip strength, PA, and ST.…”
Section: What Is Newmentioning
confidence: 99%
See 1 more Smart Citation
“…Porém estudos apontam vários fatores podem influenciar negativa ou positivamente a participação dos idosos em atividades físicas tais como socioeconómicos, ambientais e de saúde (PINTO, 2018). As principais barreiras referidas foram a limitação física, e os facilitadores o apoio formal (HETHERINGTON-RAUTH et al, 2021;JORDÃO et al, 2023;PINTO, 2018;SANTOS et al, 2012). Equipamentos como pedómetros e acelerómetros têm sido amplamente aplicados na avaliação dos padrões de atividade física em idosos.…”
Section: Introductionunclassified